2016
DOI: 10.18826/ijsets.14890
|View full text |Cite
|
Sign up to set email alerts
|

Kadın ve Erkek Lise Öğrencilerinin Beden Eğitimi ve Spor Dersine Yönelik Tutumlarının Araştırılması

Abstract: Amaç: Araştırma kadın ve erkek lise öğrencilerinin Beden Eğitimi ve Spor dersine yönelik tutumlarının belirlenmesi amacıyla yapılmıştır. Materyal ve Yöntem: Araştırma tarama modelinde bir araştırmadır. Araştırmanın evreni Burdur il merkezi ve seçilmiş ilçelerdeki lise kurumlarından, örneklem gurubu ise bu okullarda okuyan 9,10,11,12 sınıf öğrencilerden oluşmaktadır. Veriler yazılı kaynaklardan ve anket yöntemiyle elde edilmiştir. Anket olarak Güllü ve Güçlü (2009) The investigation has been made in order to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…In the literature review, Kargın Göktaş and Şentürk (2019) concluded in their study that students' attitudes were generally high. Nevertheless, there are also similar studies indicating that students have a high level of attitude toward physical education and sports (Güllü, Güçlü and Arslan, 2009;Özkurt and Pepe, 2016).…”
Section: Results Conclusion and Suggestionmentioning
confidence: 71%
See 3 more Smart Citations
“…In the literature review, Kargın Göktaş and Şentürk (2019) concluded in their study that students' attitudes were generally high. Nevertheless, there are also similar studies indicating that students have a high level of attitude toward physical education and sports (Güllü, Güçlü and Arslan, 2009;Özkurt and Pepe, 2016).…”
Section: Results Conclusion and Suggestionmentioning
confidence: 71%
“…Similarly to the results of the study, Göksel and Caz (2016) concluded in their study that gender had no significant difference in attitudes toward sports. Nevertheless, in the studies in which secondary school students' attitudes toward sports were examined, there are also studies indicating that male students' attitudes toward sports are high (Araç Ilgar and Uslu, 2018;Çelik and Pulur, 2011;Güllü, Güçlü and Arslan, 2009;Kangalgil, Hünük and Demirhan, 2006;Kargın Göktaş and Şentürk, 2019;Özkurt and Pepe, 2016;Şişko and Demirhan, 2002).…”
Section: Results Conclusion and Suggestionmentioning
confidence: 99%
See 2 more Smart Citations